The Implementation of Graduate Competency Standards in Entrepreneurship of Islamic Boarding School - Rahayu, Rizki Kusumaning; Yulianto, Arief; Prihatin, Titi (Educational Management, 2021)
The purpose of this study is to analyze the implementation of planning, organizing, commanding, coordinating, and controlling Graduate Competency Standards in entrepreneurship education at PSKQ Modern Kudus by involving all teams in achieving the vision and mission of PSKQ Modern Kudus. This case study research uses a qualitative approach. The research subjects were the leaders of the PSKQ Modern Kudus, the chairman of the PSKQ Modern Kudus foundation, the teaching staff (ustadz/ustadzah), and students. Collecting data using interview, observation, and document study methods. The research data were analyzed using the interactive model approach of Miles and Huberman (2015). Researchers tested the credibility of the data through triangulation of sources and methods. The results showed that the implementation of planning, organizing, commanding, coordinating, and controlling Graduate Competency Standards in entrepreneurship education at PSKQ Modern Kudus is currently well implemented. Planning is carried out based on the guidelines used at the international level accompanied by modifications according to the circumstances in the PSKQ Modern Kudus. Organizations have been formed and implemented according to their respective roles. Commanding is carried out by the leadership to each member involved in the existing program by providing explanations and motivation. Coordination is carried out by leaders, teaching ustadz and students in learning and projects that are being carried out either directly or indirectly. While the control is by conducting a test and depositing the work of students regarding the calligraphy that has been done and studied.